EZH2-miRNA Positive Feedback Promotes Tumor Growth in Ovarian Cancer - Liu, Ting; Cai, Jian; Cai, Jing; Wang, Zehua; Cai, Liqiong (Frontiers in Oncology, 2021)
Enhancer of zester homolog 2 (EZH2), a histone methyl transferase that mediates H3K27me3 through polycomb repressive complex 2 (PRC2), is overexpressed in ovarian cancer and promotes malignant proliferation. However, the underlying mechanism of maintaining high EZH2 expression remains elusive. Here we showed that microRNA(miRNA) inhibited EZH2 by binding to the 3′-UTR of EZH2 mRNA; conversely, EZH2 can inhibit miRNA expression. We confirmed that a feedback loop exists between EZH2 and miRNA that maintained EZH2 overexpression, thus promoting ovarian cancer proliferation in vivo and in vitro. We further explored that EZH2 inhibited miRNA expression through PRC2, as determined by CHIP(chromatin immunoprecipitation), and EZH2 decreased the expression of p21, p53 and RUNX3. These results suggest that EZH2 inhibits the expression of Et-miRNAs through the H3K27me3 pathway, thus forming an EZH2-miRNA positive feedback loop that maintains the high expression of EZH2 and promotes the malignant proliferation of cancer cells by regulating the expression of cell proliferation-related proteins.